RESPON RUMAH TANGGA MISKIN TERHADAP PELAKSANAAN PROGRAM BERAS MISKIN (RASKIN) DI KEPENGHULUAN PUJUD KECAMATAM PUJUD KABUPATEN ROKAN HILIR - Lindra Suhada; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Raskin is a food subsidy in the form of rice that is intended for poor or low-income households, as an effort by the Government to increase food security and provide social protection to target households receiving raskin. The success of the Raskin program is measured on the basis of 6T which is Exactly Targeted, Exactly Quantity, Exactly Priced, Timely, Exactly Quality, and Proper Administration. The purpose of this research is to know how the socio-economic characteristics of poor households in Kepenghuluan Pujud and see the response of poor households to the implementation of Raskin program in Kepenghuluan Pujud. The research method used is quantitative descriptive. The population of this study was all Poor Households who received the aid of Poor Rice (Raskin) in Kepenghuluan Pujud. sampling technique in this study is simple rendom sampling, this research sample amounted to 61 respondents. From the result of the research, it can be concluded that the socio-economic characteristics of Poor Households mostly work as farmers with the last education of elementary school graduates / equivalent, which has permanent type of house and the number of household heads more than 4 people, with income for family needs. Furthermore, the result of Poor Household Response to Raskin Program is a Constant Response in which the knowledge level of high poor household is 100% to the Raskin program, while the affective response is very high that is 100% while the conative response while the poor household action is less active the implementation of less active raskin program which amounted to 86.9% residing in Kepenghulan Pujud.Keywords: Response, Poor Household, Program, Poor Rice